2013
DOI: 10.1080/09540121.2013.779627
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and psychological functioning of young children of HIV-positive mothers in South Africa

Abstract: Adults with HIV are living longer due to earlier diagnosis and increased access to antiretroviral medications. Therefore, fewer young children are being orphaned and instead, are being cared for by parents who know they are HIV-positive, although they may be asymptomatic. Presently, it is unclear whether the psychological functioning of these young children is likely to be affected or, alternatively, whether it is only when a mother is ill, that children suffer adverse effects. We thus aimed to compare the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Results are consistent with research in South Africa that has shown more child behavior problems in families with children orphaned by AIDS (Cluver, Gardner, & Operario, 2007) or AIDS-symptomatic mothers (Sipsma et al, 2013). Other research has linked child behavior problems to reduced parenting skills due to increased stress associated with HIV/AIDS (Murphy, Marelich, Armistead, Herbeck, & Payne, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results are consistent with research in South Africa that has shown more child behavior problems in families with children orphaned by AIDS (Cluver, Gardner, & Operario, 2007) or AIDS-symptomatic mothers (Sipsma et al, 2013). Other research has linked child behavior problems to reduced parenting skills due to increased stress associated with HIV/AIDS (Murphy, Marelich, Armistead, Herbeck, & Payne, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Parental physical illness and child orphanhood have been shown to negatively affect positive parenting by decreasing engagement, disrupting family routines, and increasing parental absence and neglect (Armistead, Klein, & Forehand, 1995). In South Africa, HIV/AIDS-affected families are associated with increased poverty (Gillies, Tolley, & Wolstenholme, 1996), parental depression (Kuo, Operario, & Cluver, 2012), lack of social support (Casale, 2012), and increased child behavior problems (Sipsma et al, 2013). Since these factors are also associated with reduced positive parenting, they may play a mediating role in the association between HIV/AIDS and positive parenting (Andersen, 1992; Gershoff, 2007; Lovejoy, Graczyk, O'Hare, & Neuman, 2000; Pardini, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that maternal stressors associated with the onset of HIV symptoms can affect a child’s psychosocial adjustment [45,46] while other studies indicated that it is a mother’s illness or physical well being, not maternal HIV status that affects a child’s behavior (See Psychosocial paper in this series). [46] Of particular interest, is the relationship between a parent’s disclosure of their illness or HIV status and an HIV-E infant’s access to healthcare services, psychosocial adjustment and resilience. [46,47] Non-disclosure of a parent’s HIV status is associated with increased levels of depression and anxiety among HIV affected children.…”
Section: Long-term Impact Of Hiv Exposure On Infant and Childhoodmentioning
confidence: 99%
“…[46] Of particular interest, is the relationship between a parent’s disclosure of their illness or HIV status and an HIV-E infant’s access to healthcare services, psychosocial adjustment and resilience. [46,47] Non-disclosure of a parent’s HIV status is associated with increased levels of depression and anxiety among HIV affected children. [48,49]…”
Section: Long-term Impact Of Hiv Exposure On Infant and Childhoodmentioning
confidence: 99%
“…Additional communityoriented models can help to dissipate stigma, increase access to social and economic assistance, and reduce mental or psychological distress [51][52][53]. Generally, these models foster increased autonomy and self-reliance among clients and communities, directly enabling adherence and information sharing, and influencing behaviours within the community.…”
Section: Discussionmentioning
confidence: 99%